Democracy by the people : reforming campaign finance in America / edited by Eugene D. Mazo, Timothy K. Kuhner. - Kuhner, Timothy K.; Mazo, Eugene D. (Eugene David), 1973- (Cambridge University Press, 2018)
Thanks to a series of recent US Supreme Court decisions, corporations can now spend unlimited sums to influence elections, Super PACs and dark money groups are flourishing, and wealthy individuals and special interests increasingly dominate American politics. Despite the overwhelming support of Americans to fix this broken system, serious efforts at reform have languished. Campaign finance is a highly intricate and complex area of the law, and the current system favors the incumbent politicians who oversee it. This illuminating book takes these hard realities as a starting point and offers realistic solutions to reform campaign finance. With contributions from more than a dozen leading scholars of election law, it should be read by anyone interested in reclaiming the promise of American democracy.